STATUS SELENIUM DENGAN HIPETRIROIDISM: Selenium Status With Hyperthyroidism - Khatimah, Husnul; Siradjuddi, Nur Nikmah; Chaerunnimah; Amir, Aswita (Media Gizi Pangan, 2024)
Hyperthyroidism incidence has increased in recent years from 40% in 2018 to 50% in 2019, based on the annual report of Balai Litbangkes Magelang. The increase of iodine intake after fortification in the population experiencing iodine deficiency increases the risk of thyroid autoimmune, which is one of the main factors in hyperthyroid incidence. Hyperthyroid is a clinical disorder caused by the excess of thyroid hormone secretion. Adequate selenium intake is necessary to protect the thyroid from excess hydrogen peroxide. Selenium contributes to converting T4 to T3. 15% of the worldwide population suffers from selenium deficiency in which it affects thyroid hormone metabolism. One of the health problems that arise due to malabsorption of thyroid hormones is hyperthyroid. The aim of this study was to analyze the relationship between intake and serum selenium levels with TSH and FT4 levels in hyperthyroid patients using an observational method with a cross-sectional design in 50 hyperthyroid patients at the Magelang Research and Development Center with the criteria of having TSH levels below 0.3 0.3 mIU/L Those who received treatment were male and female, aged 19 to 59 years, had goiter or not. Selenium intake was obtained using the 2x24 hour recall method, while serum selenium levels were obtained through laboratory examination using the NAA method and for TSH and FT4 levels using the ELISA method. Bivariate test results using the sperm test showed that there was a significant relationship between selenium intake and TSH levels (p<0.05) in hyperthyroid patients but not with FT4 levels (p=0.088) and for serum selenium levels it was statistically significant with TSH levels and FT4 (p<0.05) hyperthyroid patients. Where the average selenium intake, serum selenium, TSH and FT4 levels were around 78.36 µg, 92.92 µg/L, 0.26 µIU/ml and 2.61 ng/dL, respectively. However, based on the results of the linear regression test, neither intake nor serum selenium levels had an impact on TSH and FT4 levels. Selenium intake and serum each have an impact on TSH or FT4 levels, but when combined together they do not have an impact on TSH or FT4 levels.